Socio-economic sustainability of Halal food production: an examination of poultry processing in Malaysia - White, Gareth R. T.; Razak, A. A.; Thomas, A. J.; Allen, Robby A. (The IJM.com, 2021)
While significant research exists in the area of sustainable food supply chains, information pertaining specifically to the Halal supply chain is limited, with very little information being available on the economic and social sustainability of Halal facilities. Through a multi-staged research methodology, this study undertakes a single company case study of a Malaysian slaughter facility. It attempts to understand the deep-rooted issues surrounding why Halal slaughterhouses struggle to maintain socio-economic sustainability even though demand for Halal food within Malaysia has increased significantly over recent years. This research contributes to the knowledge of food supply chain sustainability through exploration of the idiosyncrasies of Halal food production. It proposes and adopts a Dynamic Mapping technique that enabled the capture of internal and external process knowledge, and the simulation of what-if scenarios to determine the effect of the complex interplay of multiple systems upon the economic and social sustainability of the organization. The study finds that both external and internal issues affect the sustainability of the company. From an internal perspective, the slaughtering operation is characterized by the ritualized requirements of the Muslim faith. The slaughtering operation is the primary source of capacity constraint. Dynamic Mapping identified that with a clear lack of formalized business improvement approaches that focus on improving the bottleneck constraint, additional demand will only serve to exacerbate the situation and create a serious threat to the economic viability of the company.
Keywords: Sustainability; Supply Chain; Halal